2002
DOI: 10.1038/nature01190
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative computation in a visual neuron sensitive to looming

Abstract: Sensitivity of excitatory LGMD input to the speed of object motion. Figure S1 below illustrates an experiment that demonstrates the sensitivity of local excitatory input to theLGMD to the speed of object motion. In these experiments, a small black disk (see Krapp and Hengstenberg, Vis. Res., 1997, 37:225-234 for details) was moved at various speeds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
322
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(342 citation statements)
references
References 29 publications
17
322
3
Order By: Relevance
“…The output of these two downstream neurons would then be integrated, for example through recurrent connectivity, intracellular molecules like calcium, or extracellular molecules like neuropeptides (Durstewitz et al, 2000;Flavell et al, 2013;Major and Tank, 2004). Finally, the two integrated values are combined by divisive inhibition to yield an output that is used to control female speed (Gabbiani et al, 2002;Silver, 2010). …”
Section: Linking Computations In the Auditory Pathway With Female Behmentioning
confidence: 99%
“…The output of these two downstream neurons would then be integrated, for example through recurrent connectivity, intracellular molecules like calcium, or extracellular molecules like neuropeptides (Durstewitz et al, 2000;Flavell et al, 2013;Major and Tank, 2004). Finally, the two integrated values are combined by divisive inhibition to yield an output that is used to control female speed (Gabbiani et al, 2002;Silver, 2010). …”
Section: Linking Computations In the Auditory Pathway With Female Behmentioning
confidence: 99%
“…The best studied collision avoidance system in insects is the one of the Locust, known as the Lobula Giant Movement Detector (LGMD), which relies exclusively on vision. The LGMD has been shown to robustly signal collisions with objects independent of their size, texture, shape and approaching angle (Gabbiani et al 1999;Gabbiani 2001;Gabbiani 2002;Gabbiani 2004). Previous studies shave shown that a system that extracts visual expansion, i.e.…”
Section: Collision Avoidancementioning
confidence: 99%
“…Many sensors, from ultrasonic, infrared and laser sensors to vision have been applied to this purpose, although no general solution has been found (Fox et al 1997;Surmann et al 2003;Harrison 2005). The neural correlate of collision avoidance has been identified in many insect species, and due to its impressive performance and accessibility it has been subject of abundant research (Rowel 1971;Gabbiani 2002;Tammero & Dickinson 2002;Krapp & Gabbiani 2005). The best studied collision avoidance system in insects is the one of the Locust, known as the Lobula Giant Movement Detector (LGMD), which relies exclusively on vision.…”
Section: Collision Avoidancementioning
confidence: 99%
“…Experimental evidence for such multiplicative or modulatory interactions between neurons abounds. Gabbiani et al (2002), e.g., have verified that specific neurons of locusts perform a multiplication of two input signals. A very prominent example in higher animals are the dopaminergic modulations of cortical input to the striatum (e.g., Freund et al 1985, Nicola et al 2000.…”
Section: Physiological Background Of Dynamic Routingmentioning
confidence: 99%